(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2022)
This paper looks at different types of ornaments belonging to the selected images of the early Licchavi period while identifying, comparing, and analyzing them. It also attempts to find out ancient and local names if they have any. The images that are selected and illustrated for analytical description are excavated ones comprising a few Nepali sculptures. The majority of images are devoid of head ornamentations and are shown with heavy earrings and doughnut-shaped feet ornaments